PELATIHAN KREASI TAS GONI DARI LIMBAH PASAR UNTUK MENINGKATKAN NILAI EKONOMI PRODUK - Cisyulia Octavia Helikopta Simanjuntak; Zakiah Hidayati (LPPM UMRI, 2019)
We are facing a lot of environmental issue right now. One of the environmental problem is household and industrial waste such as plastic. Plastic waste is becoming a widely recognised environmental problem. The government of Samarinda has been banned plastic bags in grocery stores in order to reduce plastic waste as determined by Mayor Regulation No. 8 of 2019. Lots of people are looking for reusable shopping bag. One of the alternative to plastic grocery bag is burlap bag. The traditional market sellers often sell their grain in burlap sacks and may be willing to give away the unusable sacks. Burlap is very useful and has many specific application, like grocery bag and pouch. Burlap grocery bag can be adorned with patch, embroidery and beads. The aim of community service is to teach housewives to design and apply patch onto the burlap grocery bag, as traditional market waste, in order to increase the value of product. The result of the class is : improved their skill in designing and creating patch on burlap bag. It is hoped that the class will support the potential of creativity industry by reusing the waste material.